Emerging small-molecule antiviral agents in long COVID prevention - He, Xiaomeng; Zhang, Xiang; Zhong, Wu (Frontiers in Pharmacology, 2024)
Long COVID, or Post-Acute Sequelae of COVID-19 (PASC), was characterized by persistent symptoms such as fatigue, shortness of breath, and cognitive impairments.These symptoms, emerging one to two months post-infection and persisting for several months, cannot be attributed to other diagnoses. The pathophysiology of long COVID remained elusive; however, emerging studies suggested multiple potential mechanisms, including the reactivation of Epstein-Barr virus, persistent SARS-CoV-2 reservoirs, neuroinflammation, and vascular damage, which may contribute to its development.Long COVID affected multiple organ systems, including respiratory, circulatory, and nervous systems, leading to a range of functional impairments. Additionally, it showed a profound impact on mental health, manifesting as anxiety and depression, which significantly degraded the quality of life. The absence of definitive treatments underscored the importance of prevention. Recent evidence indicated that early antiviral intervention-particularly with small-molecule drugs such as Metformin, Ensitrelvir, Molnupiravir, and Nirmatrelvir-may effectively reduce the incidence of long COVID. This underscored the promising role of small-molecule compounds in mitigating long-term COVID-19 consequences, offering a novel preventive strategy against long COVID and its extensive impacts on patients.